A cross - sectional study on pharmacy student's tendency toward entrepreneurship after graduation in UiTM Malaysia - Mohammad Rosdi, Fathin Azuren (2017)
Entrepreneurship involving willingness to take risk , develop, organize and manage a business venture, idea, or good or service. An entrepreneurial spirit can be thought to include elements such as creativity, uniqueness, developing potential and business savvy. A multidimensional scale was developed and tested to assess pharmacy students' tendency toward becoming entrepreneurs within their chosen pharmacy work environments. Besides that ,it is to determine the association between socio-demographic factors with students's tendency towards becoming entrepreneurs. A descriptive, cross-sectional design was used to survey a simple random sample of fourth year BPharm students in UiTM Puncak Alam Campus. The response rate was 100% representing 130 respondents. The resulting 3- factor, 23-item Pharmacy Student Entrepreneurial Orientation (PSEO) summated scale was shown to be reliable (Cronbach alpha = 0.913) and normally distributed. Higher mean PSEO scores were found for students who choosing industry and retail independent as their first choice. Higher mean PSEO score indicate higher tendency towards entrepreneurship. There was no association between any socio-demographic factors with students' tendency towards becoming entrepreneurs. Measuring entrepreneurial orientation may help to identify students inclined to be future entrepreneurs in the profession, inform academic advising efforts, and direct attempts to foster innovation by future pharmacists.